2021
DOI: 10.3389/fpsyt.2021.576432
|View full text |Cite
|
Sign up to set email alerts
|

Therapy Processes Associated With Sudden Gains in Cognitive Therapy for Depression: Exploring Therapeutic Changes in the Sessions Surrounding the Gains

Abstract: Background: The frequency and clinical impact of Sudden Gains—large symptom improvements during a single between-session interval—in psychotherapy for depression have been well established. However, there have been relatively few efforts to identify the processes that lead to sudden gains.Aim: To explore therapy processes associated with sudden gains in cognitive therapy for depression by examining changes in the sessions surrounding the gains, and the session preceding the gain in particular.Methods: Using ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Together with the temporal pattern and newer findings (see Lemmens et al, 2021;O'Mahen et al, 2021), this contradicts the assumption of sudden gains being merely a form of random fluctuations and suggests that they mark important and meaningful points in the change process.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Together with the temporal pattern and newer findings (see Lemmens et al, 2021;O'Mahen et al, 2021), this contradicts the assumption of sudden gains being merely a form of random fluctuations and suggests that they mark important and meaningful points in the change process.…”
Section: Discussionmentioning
confidence: 69%
“…In sum, these findings show that guilt, shame and disgust might be involved in the occurrence of sudden gains, or in sustainment of gains and/or in facilitating further improvement during treatment. Together with the temporal pattern and newer findings (see Lemmens et al, 2021; O'Mahen et al, 2021), this contradicts the assumption of sudden gains being merely a form of random fluctuations and suggests that they mark important and meaningful points in the change process.…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, the prevalence of sudden gains in depressive symptoms in the present study is lower than has been reported previously. In a small clinical trial of online treatment for postnatal depression, O’Mahen et al (2017) found that 51% of participants experienced a sudden gain, and estimates of sudden gain prevalence range from 25% to 54% during face-to-face treatment (e.g., Abel et al, 2016; Lemmens et al, 2021). However, only 19% of participants experienced a sudden gain throughout online treatment in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Even though some immediate shifts in symptom presentation may occur (particularly in response to interventions like symptom prescription), this type of first-order change alone (symptom reduction) does not indicate that the paradox has been effective. However, paradigms that track rapid symptom change (from session to session) may be useful in tracking the effectiveness of PIs (Lemmens et al, 2021; Tang & DeRubeis, 1999). This suggestion is related to the systemic destabilization and reorientation that hopefully takes place during the implementation of a PI, consistent with Tang and DeRubeis’s (1999) thesis regarding sudden gains in psychotherapeutic process.…”
Section: Assessmentmentioning
confidence: 99%